Kepemanduan Keselamatan Guna Mendukung Pengembangan Beka’ Ecotourism di Pulau Masakambing - Ihsannudin, Ihsannudin; Ilma, Adihan Faizatul; Hasan, Fuad; Sriyono, Sriyono; Sunartomo, Aryo Fajar; Kuntadi, Ebban Bagus (Stupa, 2024)
Special interest ecotourism activities in small and in remote island has safety risks to visitors. Preparedness in anticipation and safety guiding skills are required. The research has aimed to determine the effect of training in improving safety guiding skills and the factors that influence it. The research was conducted at the Beka' Island Tourism Awareness Group (Pokdarwis) in Masakambing Island, Sumenep Regency, East Java. The research design uses a quantitative approach with descriptive analysis and Chi-square. The results show that only 37.5% of Pokdarwis Beka' Island members that have safety guiding competence with average score above 50. After the training there was increasing to 75% of members that have comptence of safety guiding. The variables of age, education level and position at the Pokdarwis members did not have a significant effect on increasing of safety guiding competence. Safety guiding capabilities need to be maintained by periodic training considering the potential safety risks for visitors at this destination